Malignant Peripheral Nerve Sheath Tumor in the Parapharyngeal Space: Tumor Spread through the Eustachian Tube - Lee, Jeong Hyun (AJNR Am J Neuroradiol, 2001)
Summary: We report the CT and MR findings in a patient with malignant peripheral nerve sheath tumor in the parapharyngeal space who had neither a family history nor stigmata of neurofibromatosis. A high-resolution CT scan of the temporal bone revealed bony erosion and widening of both the foramen ovale and the bony portion of the eustachian tube. A temporal bone MR image showed an intensely enhancing solid mass in the parapharyngeal space, which extended into the middle ear cavity via the eustachian tube.